Agile Methodology in Web and Mobile Based App of Tracer Study and Career Center - Djutalov, Roeslan; Irham, Muhammad; Putra, Ade Dwi; Elistiawan, Andri; Syah, Rizky Firman (Brilliance: Research of Artificial Intelligence, 2024)
This research explores the application of Agile methodology in the development of a web and mobile-based Tracer Study and Career Center application. The primary objective is to enhance the effectiveness and efficiency of career and educational tracking for users, including students, alumni, and career center staff. The study is motivated by the need to provide a responsive and adaptable solution that can continuously evolve based on user feedback and changing needs. Using Agile methodology, the development process involved iterative cycles of planning, development, testing, and evaluation, ensuring that the application meets high standards of quality and usability. Key features such as educational tracking, work experience logging, and to address the core requirements of the users. The results indicate that the Agile approach significantly improved the application's functionality and user experience. However, further enhancements in the user interface and additional feature adjustments based on ongoing user feedback are necessary. The research concludes that Agile methodology is effective in developing adaptive and user-centered applications, though it highlights the importance of continuous improvement and comprehensive user engagement in future developments. This study provides valuable insights for developers and researchers in the field of educational and career management applications, demonstrating the practical implications of Agile in creating responsive and effective software solutions.